Passive transfer of antibodies to the linear epitope 60 kD Ro 273–289 induces features of Sjögren's syndrome in naive mice. (April 2015) - Maier‐Moore, J. S.; Kurien, B. T.; D'Souza, A.; Bockus, L.; Asfa, S.; Dorri, Y.; Hubbell, S.; Yeliosof, O.; Obeso, D.; Schoeb, T. R.; Jonsson, R.; Scofield, R. H.
Summary Sjögren's syndrome (SS) is an autoimmune inflammatory disease that primarily affects the lacrimal and salivary glands causing dry eyes and mouth. Antibodies to Ro60 are observed frequently in patients with SS; however, the role of these antibodies in SS initiation and progression remains unclear. The sequence Ro60 273–289 (Ro274) is a known B cell epitope of Ro60 and antibodies to this epitope have been observed in a subset of SS patients and in animals immunized with Ro60 protein. Animals immunized with Ro274 linear peptide develop a Sjögren's‐like illness. We hypothesized that passive transfer of anti‐Ro274‐specific immunoglobulin (Ig)G would induce a Sjögren's‐like phenotype. To evaluate this hypothesis, we adoptively transferred affinity‐purified Ro274 antibodies into naive BALB/c animals, then evaluated salivary gland histology, function and IgG localization 4 days post‐transfer. At this time‐point, there was no demonstrable mononuclear cell infiltration and salivary glands were histologically normal, but we observed a functional deficit in stimulated salivary flow of animals receiving Ro274 antibodies compared to animals receiving control IgG. Cellular fractionation and enzyme‐linked immunosorbent assay revealed Ro274‐specific antibodies in the nucleus and cytoplasmic fractions of isolated parotid salivary gland cells that was confirmed by immunohistochemistry. These data support the hypothesis that antibodies to Ro274 deposit in salivary glands can enter intact salivary gland cells and are involved in the dysregulation of salivary flow in SS.